Students' Self-Efficacy in Public Speaking: A Case Study in Indonesian EFL Context - Tahtania Regita Dwi Noer Agustin; Dede Pertamana; Rahmat Rahmat (TLEMC (Teaching and Learning English in Multicultural Contexts), 2022)
This study aims to investigate students’ self-efficacy in public speaking. This study involved four participants. The data collection method used is in the form of semi-structured interviews, then the data will be analyzed using thematic analysis. The research results are divided into four sources of self-efficacy from Bandura, namely Enactive Mastery Experience, Verbal Persuasion, Vicarious Experience, and Physiological and Affective States. This finding discusses the final level of students' confidence in their self-efficacy. Therefore, the results of this study provide empirical insight for students about self-efficacy beliefs of Enactive Mastery Experience (EME), Vicarious Experience (VE), Verbal Persuasion (VP), and Physiological and Affective State (PAS) and also provide information for teachers to optimize future learning, especially regarding self-efficacy.Keywords: Self-Efficacy, Source Self-Efficacy, Public Speaking